Analysis of the Influence of Service Access on the Utilization of Health Services at Community Health Centers - Miftahul Jannah; Wibowo, Hendry (Journal of Health Management, Administration and Public Health Policies, 2024)
Health service accessibility regulations play a crucial role in determining the level of health service utilization in the community. Health centers provide health services to the community, while efforts to improve access to health services are important factors for quality health, including improving access to basic health services. The purpose of this study is to analyze the effect of service access on the utilization of health services in health centers. This study uses the method of Retrospective Observation, namely with a qualitative approach in Systematic Review to synthesize the research results. Literature searches are carried out online from Google Scholar and Publish and Perish using the keywords "Service Access, Health Services." Health services are very important for the community, especially access and utilization of health services in health centers; therefore, to increase the utilization of health center services, efforts that need to be made are that health centers need to run a mobile health center program as an alternative to facilitate access to health services, especially for people with very poor economic status so that they can access health center services without financial barriers such as transportation costs. It can be concluded that there is an influence of access to health services on the utilization of services at health centers. Keywords: Access to services, Utilization of Health Services, Health Centers